4-nitroquinoline 1-oxide-induced oral epithelial lesions exhibit time- and stage-dependent changes in the tumor immune microenvironment - Sellæg, Kjersti; Schwienbacher, Ruth; Kranz, Mathias; Aamodt, Anna Engan; Wirsing, Anna M.; Berge, Gerd; Hadler-Olsen, Elin; Magnussen, Synnøve Norvoll (Frontiers in Oncology, 2024)
Oral tongue squamous cell carcinoma (OTSCC) is the most common cancer of the oral cavity and is associated with high morbidity due to local invasion and lymph node metastasis. Tumor infiltrating lymphocytes (TILs) are associated with good prognosis in oral cancer patients and dictate response to treatment. Ectopic sites for immune activation in tumors, known as tertiary lymphoid structures (TLS), and tumor-associated high-endothelial venules (TA-HEVs), which are specialized lymphocyte recruiting vessels, are associated with a favorable prognosis in OSCC. Why only some tumors support the development of TLS and HEVs is poorly understood. In the current study we explored the infiltration of lymphocyte subsets and the development of TLS and HEVs in oral epithelial lesions using the 4-nitroquinoline 1-oxide (4NQO)-induced mouse model of oral carcinogenesis. We found that the immune response to 4NQO-induced oral epithelial lesions was dominated by T cell subsets. The number of T cells (CD4+, FoxP3+, and CD8+), B cells (B220+) and PNAd+ HEVs increased from the earliest to the latest endpoints. All the immune markers increased with the severity of the dysplasia, while the number of HEVs and B cells further increased in SCCs. HEVs were present already in earlystage lesions, while TLS did not develop at any timepoint. This suggests that the 4NQO model is applicable to study the dynamics of the tumor immune microenvironment at early phases of oral cancer development, including the regulation of TA-HEVs in OTSCC.